Fenomenul recidivei în România - Dâmboeanu, Cristina (Calitatea Vieții, 2011)
The article approaches a problem of wide theoretical and practical interest, such as recidivism, having as starting point the observation that in Romania, few researches were dedicated to the analysis of the recidivism extent, its forms of manifestation and its causes and favourable conditions. The study presents the evolution of the phenomena in our country and also, the main deficiencies of the current penitenciary system, as it results from the interviews with the psychologists and the social workers from the Giurgiu, Mărgineni and Târgşor Penitenciaries.